Modeling and Correcting Cure‐Through in Continuous Stereolithographic 3D Printing. Issue 12 (21st October 2019) - Pritchard, Zachary D.; de Beer, Martin P.; Whelan, Riley J.; Scott, Timothy F.; Burns, Mark A.
Abstract: Continuous stereolithography offers significant speed improvements over traditional layer‐by‐layer approaches but is more susceptible to cure‐through, undesired curing along the axis of exposure. Typically, cure‐through is mitigated at the cost of print speed by reducing penetration depth in the photopolymer resin via the addition of nonreactive light absorbers. Here, a mathematical approach is presented to model the dose profile in a part produced using continuous stereolithography. From this model, a correction method is developed to modify the projected images and produce a chosen dose profile, thereby reducing cure‐through while maintaining print speed. The method is verified experimentally on a continuous stereolithographic 3D printer, and the practicality of various dose profiles is investigated. In optimizing the critical dose parameter, the measured gelation dose D gel is found to be insufficient for accurate reproduction of features, and an optimal value of D c = 5 D gel is chosen for the test resin. Using optimized parameters with a high‐absorbance height resin ( h a = 2000 µm), feature height errors are reduced by over 85% in a test model while maintaining a high print speed ( s = 750 mm h −1 ). Abstract : A model for optical dose in continuous stereolithography is developed and used to improve dimensional accuracy for high‐speed, low‐absorbance resins, which are susceptible to additional curing on the surface of designed features. By modifying the projected images, a prescribed dose profile can be applied throughout the printed part. Print fidelity is improved while maintaining high fabrication rates.